Interaction relationship of major dietary patterns and adiponectin gene polymorphisms on biochemical parameters in healthy pregnant women and those with gestational diabetes - Hamed Mir; Abazar Roustazadeh; Sima Jafarirad; Farideh Mogharab; Seyed Ahmad Hosseini; Amir Abdoli; Saiedeh Erfanian (Mashhad University of Medical Sciences, 2022)
Introduction: A healthy diet plays an important role in the prevention of gestational diabetes (GDM); the genetic background is also effective in the pathogenesis of GDM. Adiponectin is a hormone that has a wide range of effects on carbohydrate, fat and protein metabolism. This study was performed aimed to investigate the interaction effect of major dietary patterns and adiponectin gene polymorphism on biochemical factors in healthy pregnant women and those with gestational diabetes. Methods: This case-control study was performed in 2018-2019 on pregnant women referring to the gynecological ward of hospitals/clinics in Jahrom city, Fars province. 387 healthy pregnant women and 306 pregnant women with GDM completed the food frequency questionnaire. The principal component analysis method was used to extract the major dietary patterns. In addition, blood biochemical factors were measured and genomic DNA was extracted. PCR-RFLP technique was used to identify rs266729 polymorphism of adiponectin gene. Data were analyzed using SPSS (version 22.0). Multifactorial analysis of variance was use to study the interaction of major dietary patterns and adiponectin gene polymorphisms with different biochemical factors. P<0.05 was considered statistically significant. Results: No significant relationship was observed between the frequency of rs266729 polymorphism and GDM (p> 0.05). The level of high density lipoprotein-cholesterol (HDL-C) in the quartiles of the "Fruits and Dairy Products" dietary pattern showed a significant difference in GDM women (p = 0.048). Fasting blood sugar and triglyceride levels in the quartiles of the "Fruits and Dairy Products" dietary pattern showed significant differences for different rs266729 polymorphism genotypes in the gestational diabetes group (p-interaction: 0.033 and 0.002, respectively). Conclusion: in accordance with the adiponectin genotype in pregnant women, consumption of balanced amounts of fruits and dairy products has an effective role in preventing GDM.